A role for retro-splenial cortex in the task-related P3 network - Das, Diptyajit; Shaw, Marnie; Hämäläinen, Matti; Dykstra, Andrew R.; Doll, Laura; Gutschalk, Alexander (Clinical neurophysiology, 2024)
Objective - The P3 is an event-related response observed in relation to task-relevant sensory events. Despite its ubiquitous presence, the neural generators of the P3 are controversial and not well identified. - Methods - We compared source analysis of combined magneto- and electroencephalography (M/EEG) data with functional magnetic resonance imaging (fMRI) and simulation studies to better understand the sources of the P3 in an auditory oddball paradigm. - Results - Our results suggest that the dominant source of the classical, postero-central P3 lies in the retro-splenial cortex of the ventral cingulate gyrus. A second P3 source in the anterior insular cortex contributes little to the postero-central maximum. Multiple other sources in the auditory, somatosensory, and anterior midcingulate cortex are active in an overlapping time window but can be functionally dissociated based on their activation time courses. - Conclusions - The retro-splenial cortex is a dominant source of the parietal P3 maximum in EEG. - Significance - These results provide a new perspective for the interpretation of the extensive research based on the P3 response.
Online verfügbar: 28. November 2023
Gesehen am 21.02.2024